Critical advances for the iron molten air battery: a new lowest temperature, rechargeable, ternary electrolyte domain. Issue 42 (24th September 2015) - Liu, Shuzhi; Li, Xin; Cui, Baochen; Liu, Xianjun; Hao, Yulan; Guo, Qi; Xu, Peiqiang; Licht, Stuart
Abstract : The iron molten air battery cycled stably at 500 °C for 60 cycles using cost effective nickel and steel electrodes and KCl–LiCl–LiOH eutectic electrolyte with added NaOH. Abstract : A new rechargeable iron molten air battery is demonstrated for large-scale energy storage. The operational temperature range of the battery is lowered by 230 °C using a KCl–LiCl–LiOH eutectic electrolyte with added NaOH. The battery cycled stably at 500 °C for 60 cycles with an average discharge potential of ∼1.04 V and average charging potential of ∼1.21 V. When the active interface area for the oxygen reduction reaction on the air electrode is improved, 85.2% coulombic efficiency is obtained and also 99.1% to a 0.5 V discharge cutoff. The iron molten air battery has advantages of higher capacity, low cost, sustainability, and environmental friendliness compared to existing secondary batteries.